Poor People’s Perceptions of Government Support for Entrepreneurship and Small Business Promotion in a Developing Country - Meyer, Natanya (Journal of Economics and Behavioral Studies, 2015)
Unemployment is a global concern; therefore many developing countries focus on entrepreneurship development and small business promotion as a possible solution. Entrepreneurs are regarded as drivers of the economy as they not only provide income for themselves but also create job opportunities for other people. The South African Government focuses on job creation as a priority, involving many strategies and policies. However, many marginalised and impoverished people still do not benefit from these policies. The central purpose of this article is to analyse poor people’s perceptions of the role of government in creating jobs and assistance in providing entrepreneurial skills training and support. A socioeconomic household survey, consisting of approximately 3200 households, was conducted within various areas in the Metsimaholo, Moqhaka, Ngwathe and Mafube Local Municipalities, all located in the rural Northern Free State region in South Africa. Results of the survey show that 68.3% of participants feel that government is not doing enough to create jobs while a total of 49.1% indicated that government could assist in job creation by providing entrepreneurial skills training. A total of 56.2% indicated that they would like to open a small business. Improved government support and initiatives could lead to many poor households generating their own income through entrepreneurial activities.